Education actions in emergencies during the armed conflict and the pandemic, case: San José del Guaviare 2002 – 2021 - Zuluaga Trujillo, Gustavo Antonio (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective: To analyze practices of Education in Emergencies carried out by national organizations such as the Ministry of National Education and international organizations such as UNESCO, Save the Children, the Inter-agency Network for Education in Emergency Situations, as well as by teachers during the 2002-2018 period of the Colombian armed conflict.   Originality/ contribution:  the approach to Education in Emergencies in the period of conflict and post-agreement (2016-2018), and the impact of the pandemic to contextualize the present time. Although it is not in the temporal estimation, it is offered as a contribution to other forms of Education in Emergencies different from those arising from the armed conflict and which may be useful for the development of educational programs in the post-agreement time.    Method: the research is based on the qualitative paradigm, epistemologically grounded on the Gadamerian hermeneutic historical model, as well as on the documentary and phenomenological models.   Strategies/information collection: life stories of teachers from San José del Guaviare are used for the hermeneutic interpretation. These stories were collected and analyzed through interviews, review of archives and compilations of anecdotes published by teachers of the educational community of Guaviare since the beginning of the 21st century.   Conclusions: according to the analysis of the answers obtained in the interviews and taking into account the Gadamerian perspective, it is concluded that the experience of Education in Emergencies, carried out in Guaviare, favorably impacted and supported resilient populations in the region.